Participación ciudadana en la elaboración de los planes especiales de uso y ocupación del suelo (Peuos), parroquia de Yaruquí, :Caso comuna de Oyambarillo - Rosero, Germán Patricio (2015)
The subject of theory, “Citizen participation in the elaboration of special plans of use and occupation of the land, parish of Yaruqui, case commune of Oyambarillo” responds as a result of the territorial ordinance plan and the instruments of territorial planning fully compliant by the Metropolitan Municipality District of Quito, plans that have not been a positive response to community demands to solve their problems of endowing of basic services and urban infrastructure given that the referred plans are not according with the urban conditions according with the urban conditions in the territory, in another words not reflect the reality territory of industry in which it is intended applying the rules in the zoning plan the parameters as are: land occupation coefficient, land use and minimum lot frontage and principal use, etc. This situation has induced stagnation in the territory development, speculation in the land value, land traffic, lack of public and private investment that contribute improve quality of life of the inhabitants.